Review of salivary antioxidants and their barriers - Nelson, Ashlianne; Santosh, Arvind Babu Rajendra; Jones, Thaon (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Oxidative stress results from the imbalance between reactive oxygen species (ROS) and cellular antioxidant defenses. Oxidative stress can cause damage to cellular structures such as cell membranes, lipids, proteins, lipoproteins, and deoxyribonucleic acids when free radicals are present in excess. Antioxidant mechanisms protect tissues against oxidative stress by decreasing free radical levels in cells through the inhibition of activities or expression of free radical-generating enzymes. Purpose: The purpose of this paper is to discuss the role of antioxidants in protecting cells from the harmful effects of ROS, particularly in the context of oral mucosa, and to clarify which molecules disrupt the pathway of these antioxidants. Review: Salivary peroxidase, catalase, superoxide dismutase, and glutathione reductase are enzymatic salivary antioxidants, and uric acid, reduced glutathione, albumin, and lactoferrin are non-enzymatic antioxidants. Both types of antioxidants regularly donate an electron to free radicals to reduce their levels in cells. Conclusion: Antioxidant activities may be disrupted by signaling mechanisms resulting from barrier regulations observed in tissue. The increased expression of malondialdehyde is an indicator of disrupted antioxidant barriers.